How resilience innovations in food supply chains are revolutionizing logistics, wholesale trade, and farm services in developing countries - Reardon, Thomas; Vos, Rob (Wageningen University & Research, 2023)
Developing country food supply chains have been pummeled by a series (and often a confluence) of shocks over the past several decades, including the Russia-Ukraine war, COVID-19, climate shocks from hurricanes to floods to droughts, animal and plant diseases, an intensification of road banditry and local conflicts, and overlaying all these, deep transformation in markets themselves with new requirements for quality and food safety. Yet supply chains have been largely resilient, adapting and bouncing back in surprising ways. We show that this has often involves deep ‘pivoting’ by one segment or one value chain, and ‘co-pivoting’ by another to facilitate the former’s pivot. We present a conceptual framework and then illustrate with a variety of examples from Africa and Asia, such as pivoting toward e-commerce by Asian retailers and co-pivoting by delivery intermediaries; pivoting toward quality horticultural production by African and Asian farmers and co-pivoting by mobile outsource services for farming and marketing; and building of redundant ports to protect rice milling operations from climate shocks in Asia by agribusiness and logistic firms. The paper provides implications for policy to facilitate these adaptions and for resilience strategies of agribusiness firms.